The Effects of Parenting and Temperament Similarity Among Adolescent Siblings on Positive Family Relationships - Shi, Xinxin; Campione-Barr, Nicole (Frontiers in Psychology, 2021)
The detrimental effects of parental differential treatment have been shown in previous research, but fewer researchers have pointed out that differential treatment does not always lead to negative outcomes. Thus, the present study examines the role of temperament similarity on the association between parenting similarity and positive family relationship qualities over 1 year in 145 adolescent sibling dyads (Mfirst−born = 14.97 and SD = 1.68 years; Msecond−born = 12.20 and SD = 1.92 years). Latent moderator structure models (LMS) showed that a higher level of parenting similarity was related to more positive family relationships when siblings were more similar in their temperaments; however, a lower level of parenting similarity was related to more positive relationship qualities with family members 1 year later in the context of less sibling temperament similarity.